Problems and Accommodation Strategies Reported by Computer Users with Rheumatoid Arthritis or Fibromyalgia. - Baker, Nancy; Rubinstein, Elaine; Rogers, Joan (Journal of Occupational Rehabilitation, 2012)
Introduction: Little is known about the problems experienced by and the accommodation strategies used by computer users with rheumatoid arthritis (RA) or fibromyalgia (FM). This study (1) describes specific problems and accommodation strategies used by people with RA and FM during computer use; and (2) examines if there were significant differences in the problems and accommodation strategies between the different equipment items for each diagnosis. Methods: Subjects were recruited from the Arthritis Network Disease Registry. Respondents completed a self-report survey, the Computer Problems Survey. Data were analyzed descriptively (percentages; 95% confidence intervals). Differences in the number of problems and accommodation strategies were calculated using nonparametric tests (Friedman's test and Wilcoxon Signed Rank Test). Results: Eighty-four percent of respondents reported at least one problem with at least one equipment item (RA = 81.5%; FM = 88.9%), with most respondents reporting problems with their chair. Respondents most commonly used timing accommodation strategies to cope with mouse and keyboard problems, personal accommodation strategies to cope with chair problems and environmental accommodation strategies to cope with monitor problems. Conclusions: The number of problems during computer use was substantial in our sample, and our respondents with RA and FM may not implement the most effective strategies to deal with their chair, keyboard, or mouse problems. This study suggests that workers with RA and FM might potentially benefit from education and interventions to assist with the development of accommodation strategies to reduce problems related to computer use.